Effect of Varying Levels of Fish Amino Acid (FAA) on the Growth and Yield of Yellow Corn (Zea mays L.) in Sulu, Philippines - Muksidal Lakibul Hasim; Alwajir O. Tuttuh; Nedzfa Abdurahman Ahajani; Neriza J. Kiram; Abey K. Sobrepeńa; Rasmalyn Sarahan Samla; Amrija A. Saradi; Mohammad Jamal A. Saradi; Fatima Sheirene M. Marajuli (Future Science / FSH-PH Publications, 2026)
This study aimed to determine how different amounts of Fish Amino Acid (FAA) affected the growth, yield, and profitability of Yellow Corn (Zea mays L.). The experiment was conducted at the Integrated Farming Production Center in Langtad, Indanan, Sulu, Philippines, at Mindanao State University – Sulu, College of Agriculture, from June 21 to September 25, 2023. Four treatments were analyzed in this research: 350 ml of FAA, 300 ml of FAA, and 250 ml FAA with a control group (without treatment) using Randomized Complete Block Design (RCBD) consisting of three replications. In this case, the FAA was produced from sardine waste with molasses (at a ratio of 1:1) and used in foliar spraying every second week. Measurements of growth included plant height, leaf number and length (table 4), while yield measurements included ear length (with and without husk), total number and weight per unit area for harvested ears, as well as return on investment (ROI).